2021
DOI: 10.1093/ofid/ofab307
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Outcomes Related to the Use of Guideline-Recommended Antibiotics in Patients With Neutropenic Fever at the Uganda Cancer Institute

Abstract: Background Neutropenic fever (NF) is associated with significant morbidity and mortality for patients receiving cancer treatment in sub-Saharan Africa (sSA). However, the antibiotic management of NF in sSA has not been well described. We evaluated the timing and selection of antibiotics for patients with NF at the Uganda Cancer Institute (UCI). Methods We conducted a retrospective chart review of adults with acute leukemia ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, we and our colleagues found that more than 50% of the bacteria isolated from Ugandan patients with neutropenic fever were resistant to the first-line antibiotics recommended in the US-based neutropenic fever guidelines. 9,10 As a result, the 30-day mortality rate for patients with neutropenic fever was 46% to 54%, 10,11 which contrasts starkly with the 2.6% to 21.4% mortality rate-depending on the number of comorbidities-for patients being treated in the United States. 12 As highlighted by our case, research studies may be one of the few avenues through which patients have access to affordable laboratory diagnostics.…”
Section: Diagnostic Inequitymentioning
confidence: 92%
“…For example, we and our colleagues found that more than 50% of the bacteria isolated from Ugandan patients with neutropenic fever were resistant to the first-line antibiotics recommended in the US-based neutropenic fever guidelines. 9,10 As a result, the 30-day mortality rate for patients with neutropenic fever was 46% to 54%, 10,11 which contrasts starkly with the 2.6% to 21.4% mortality rate-depending on the number of comorbidities-for patients being treated in the United States. 12 As highlighted by our case, research studies may be one of the few avenues through which patients have access to affordable laboratory diagnostics.…”
Section: Diagnostic Inequitymentioning
confidence: 92%
“…Treatment guidelines have largely relied on evidence from high-income countries,3 unpublished data from treatment centres and anecdotal experience. The barriers to and facilitators of effective management which contribute to the high death rate of fevers in paediatric patients with cancer in SSA are currently unknown 9 18…”
Section: Introductionmentioning
confidence: 99%
“…Empirical antibiotics therapy is standard practice in the treatment of NF. 9 , 10 However, there is a significant debate about the selection of initial antibiotic regimens. 3 The initial regimen in seriously ill patients should cover both gram-positive and gram-negative pathogens and should be administered intravenously.…”
Section: Introductionmentioning
confidence: 99%